[tex]\displaystyle\bf\\\frac{x-25}{x+5\sqrt{x} } =\frac{(\sqrt{x} )^{2} -5^{2} }{(\sqrt{x} )^{2} +5\sqrt{x} } =\frac{(\sqrt{x} -5)\cdot(\sqrt{x} +5)}{\sqrt{x} \cdot(\sqrt{x} +5)} =\\\\\\=\frac{\sqrt{x} -5}{\sqrt{x} }[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
[tex]\displaystyle\bf\\\frac{x-25}{x+5\sqrt{x} } =\frac{(\sqrt{x} )^{2} -5^{2} }{(\sqrt{x} )^{2} +5\sqrt{x} } =\frac{(\sqrt{x} -5)\cdot(\sqrt{x} +5)}{\sqrt{x} \cdot(\sqrt{x} +5)} =\\\\\\=\frac{\sqrt{x} -5}{\sqrt{x} }[/tex]